Respuesta :

Answer:

B)  ( x +  3y)²

Step-by-step explanation:

u = x + y    ;  v =  x + 5y

uv = ( x + y ) * ( x + 5y)                

    = x * ( x + 5y) + y * (x + 5y)                    [ x * ( x + 5y) = x*x + x*5y = x² + 5xy]

    = x² + 5xy  + xy  + 5y²

   uv  = x² + 6xy + 5y²----------equ 1

v - u =   x + 5y - ( x+y)

       = x + 5y - x - y

       =  4y

(v-u)² = (4y)² = 16y²

[(v-u)/2]² = 16y² / 2²

              = 16y² / 4 = 4y²

[(v-u)/2]² =  4y²     ----------- equ 2

uv + [(v-u)/2]² = x² + 6xy + 5y² + 4y²      ( from equ 1 and equ 2)

                     = x² + 6xy + 9y²

                     = ( x +  3y)²